The Influence of Service Quality and Price Perception on Brand Image and Their Impact on Purchase Intention(A Study of Bread and Cake Shops in Sinabang) (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to examine the influence of service quality and price perception on brand image and their impact on purchase intention, focusing on bread and cake shops in Sinabang. A non-probability sampling technique, specifically purposive sampling, was employed. The sample size was determined based on the rule of ten times the number of indicators used in the study. Since the research utilized 21 indicators, the minimum required sample size was 210 respondents (10 × 21 = 210), all of whom were customers of bread and cake shops in Sinabang. Data were measured using a five-point Likert scale. Descriptive analysis was conducted using SPSS, while direct hypothesis testing was performed using the SEM-AMOS method. Indirect hypothesis testing was carried out using the Sobel test. The results indicate that, descriptively, all research variables fall within the “good” category. Regarding direct effects, service quality has a positive influence on brand image, whereas price perception does not have a significant effect on brand image. Purchase intention is positively influenced by both service quality and brand image, while price perception negatively affects purchase intention. Mediation analysis reveals that brand image partially mediates the relationship between service quality and purchase intention; however, brand image does not mediate the relationship between price perception and purchase intention.